Computational Literary Analysis of Hamlet: Emotional Mechanisms Behind Hamlet’s And Ophelia’s Tragic Ends - bouzar, abdelouahd; El Idrissi, Khaoula; Ghourdou, Tayeb (International Journal of Language and Literary Studies, 2025)
This study investigates the emotional mechanisms driving the tragic demises of Hamlet and Ophelia in Shakespeare’s Hamlet through a mixed-methods approach that integrates computational sentiment analysis with qualitative thematic coding. By applying sentiment trajectory mapping, emotion co-occurrence networks, and parallel coordinates visualization, the research identifies distinct emotional patterns that characterize each character’s psychological journey. The findings demonstrate that Hamlet’s downfall stems primarily from the interplay between doubt and suspicion with anger and vengefulness, producing a cycle of hesitation and impulsive action. In contrast, Ophelia’s demise is dominated by grief and despair, intensified by her social powerlessness and lack of agency, which ultimately overwhelms her emotional resilience. These divergent emotional drivers highlight how gender and social position shape Shakespeare’s portrayal of psychological deterioration. The study not only contributes to Shakespearean scholarship by offering empirical support for long-standing interpretive claims but also advances computational literary analysis by demonstrating how digital humanities tools can illuminate nuanced psychological dynamics in canonical texts.